Западня, или Исповедь девственницы: роман / К. Васильева - Васильева Ксения (Русский романс, 2009)
Экземпляры: ф.6 (09.09.2009) / Инвентарный номер: 44040 / Цена: 65.00 / Авт.знак: В 19 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6